Contrasting energy pathways suggest differing susceptibility of pelagic fishes to an invasive ecosystem engineer in a large lake system - Chiapella, Ariana; Possamai, Bianca; Marsden, J. Ellen; Kainz, Martin J.; Stockwell, Jason D. (Frontiers in Ecology and Evolution, 2023)
Species invasions can lead to ecological regime shifts by altering food web structure and changing nutrient cycling. Stable isotopes are a powerful tool to understand the potential and realized impacts of invasive species on food webs, especially when used in tandem with other dietary tracers. An invasion by one of the most notorious freshwater invaders in North America, the quagga mussel (Dreissena bugensis), is imminent in Lake Champlain, USA. An invasion by this filter feeder has the potential to drastically alter energy pathways and destabilize pelagic fisheries via bottom-up impacts. However, the extent and magnitude of these impacts depend on the current food web structure of the mid-trophic pelagic food web, which was previously not well described. We used bayesian stable isotope mixing models informed by stomach content analysis, fatty acid analysis, and deuterium stable isotopes of fatty acids to identify which energy pathways are most important to mid-trophic fishes. We determined that in the main basin of the lake, the spring phytoplankton bloom and deep chlorophyll layer - the resources most vulnerable to quagga mussels - provide a disproportionate amount of support to the pelagic food web via zooplankton and the migrating invertebrate Mysis. The food web in the northeast basin of the lake is supported by epilimnetic phytoplankton, which is more protected from the filtration effects of quagga mussels, but this basin would likely not provide high quality foraging refuge to coldwater pelagic fish due to unfavorable oxythermal conditions. The mid-trophic food web of Lake Champlain - and consequently piscivores who rely on these prey - may be vulnerable to the impending quagga mussel invasion if migratory Mysis are not able to shift their diet to benthic resources.